The Code of Colorado Springs: Comprising Article XX of the Constitution of the State of Colorado, the Charter, Amendments Thereto, and General Ordinances of the City of Colorado Springs, Colorado 274-75, § 506 (Frank Exline ed., 1914) - (:unkn) unknown (My University, 1914)
It shall be unlawful for any person within the corporate limits of the city of Colorado Springs, to have in possession, use, sell or give away any instrument, toy or weapon commonly known as a toy pistol, using fulminate paper caps or copper shelled blank cartridges, or to have in possession, use, sell or give away any explosive bombs known as cannon firecrackers.
Keywords: TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES